Hubungan Kesehatan Mental Dengan Status Ibu Tidak Menyusui Di Kabupaten Banyumas - Fauziah Hanum Nur Adriyani; Arlyana Hikmanti; Feti Kumala Dewi (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
A mother's mental health greatly impacts breastfeeding and child growth health. Due to the high rate of discontinuation of breastfeeding, we aimed to assess the relationship between maternal mental health and breastfeeding status and find underlying psychological disorders. This will enable us to improve the health of children, mothers, and families communities by adjusting and controlling for factors contributing to the cessation of breastfeeding. This study uses analytical methods. The research sample includes mothers who stopped breastfeeding, used formula milk for babies and toddlers, and used mixed methods (breast milk and formula) for babies aged 0-6 months. The mental health data collection method was adopted from GHQ-28 (General Health Questionnaire). Data analysis used descriptive statistics (absolute frequency, relative frequency, mean, standard deviation) and OR test, Chi-square or Mann-Whitney test. The results showed that mental health influenced the reasons for mothers not breastfeeding because the baby was small 74%, the baby did not gain weight 55.2%, the mother because she worked 77.4%, lack of support 95.3%, breastfeeding was not. Did not come out as much as 89.8%. There were 21 (29.5) mental health problems for working mothers, and 23 (41.1%) breast milk did not come out smoothly, which had an effect of 30,286 times which was the main reason for mothers not coming out.